Intermittent Catheterization Frequency and Interval in Children: Are We Clear Enough? - Ghahestani, Seyyed Mohammad; Karimi, Sara (Urology Journal, 2021)
Abstract: Intermittent catheterization has been introduced as a lifesaving management strategy in cases of bladder neuromuscular dysfunction both in adults and children. Surprisingly there are scarce data or even clear professional opinions about interval and frequency of catheterization attempts in children. This may have a considerable impact specially in children with vastly variable bladder capacity and function. We tried to throw light on this problem, suggest a simple estimation and propose a more frequent catheterization schedule than commonly perceived, as an either temporizing or extenuating resort before cystoplasty in some cases.